Effects of cobalt-60 gamma irradiation on microbial contaminants and phytochemical constituents of different medicinal plants - Mhd Jamal, Syafiqah (2020)
Medicinal plants have been utilized worldwide for many centuries to treat diseases and enhance human’s health since they are rich in phytochemical constituents. Nowadays, medicinal plants still play an important role in healthcare sectors across many countries include Europe and Southeast Asia. Recently, medicinal plants such as Eurycoma longifolia, Ficus deltoidea and Centella asiatica have been widely commercialized as herbal-based products in Malaysia. However, high occurrence of microorganisms in medicinal plants can cause hazards to the consumers and change the therapeutic effects. For this reason, the study is focused on the effectiveness of cobalt-60 gamma irradiation in reducing the microbial contaminants and preserving the phytochemical constituents in common medicinal plants; Orthosiphon aristatus (Blume) Miq., Labisia pumila and Piper betle L. This study provides preliminary data on the effectiveness of gamma irradiation as an efficient food sterilizer and provide specific dosages to sterilize herbs in Malaysia. The medicinal plants were processed as powder, individually packaged and exposed to 0, 3, 6, 9 and 12 kGy cobalt-60 gamma irradiation at Malaysia Nuclear Agency. The microbial contaminants present in non-irradiated and irradiated medicinal plants were evaluated at 0, 3 and 6 months by conducting the microbial enumeration tests; Total Aerobic Microbial Counts (TAMC) and Total Yeast and Mold Counts (TYMC), bacterial identification using selective media and 16S rRNA PCR amplification. The microbial enumeration tests results showed that the bacterial, yeast and mold loads were significantly reduced after irradiation. There were significant changes (P < 0.05) observed in the microbial counts after irradiation at 3 and 6 kGy, whereas no significant changes (P > 0.05) observed after higher dosages. Interestingly, P. betle showed low microbial loads (< 102 CFU/g) and no significant changes (P > 0.05) were observed pre- and post- irradiation. The identification results revealed the presence of bacteria from Gammaproteobacteria and Clostridia classes in non-irradiated O. aristatus and L. pumila, while bacteria from Bacilli class mostly isolated from irradiated medicinal plants. Dose of 6 kGy was able to eliminate pathogenic Bacillus cereus in O. aristatus, whereas 9 kGy was able to eliminate pathogenic B. cereus in L. pumila. Interestingly, no pathogenic bacteria detected in P. betle pre- and postirradiation. The data clearly showed that gamma irradiation dose is plantdependent where irradiation at 6 and 9 kGy were needed to eliminate pathogenic bacteria in O. aristatus and L. pumila, respectively. This highlights that specific dosages are needed in eliminating pathogenic bacteria in different medicinal plants. Meanwhile, P. betle is considered as a microbial low plant and gamma irradiation seems not necessary to be applied on the plant. Concurrently, there were no changes in the phytochemical contents of medicinal plants in which constituents including saponins, tannins, steroids and triterpenes were detected in both non-irradiated and irradiated medicinal plants. In conclusion, cobalt-60 gamma irradiation is effective in reducing the microbial contaminants in medicinal plants and maintaining the phytochemical constituents.